Utilization of research findings for health policy making and practice: evidence from three case studies in Bangladesh - Walugembe, David Roger; Kiwanuka, Suzanne N.; Matovu, Joseph K. B.; Rutebemberwa, Elizeus; Reichenbach, Laura (Health Research Policy and Systems, 2015)
In striving to contribute towards improved health outcomes, health research institutions generate and accumulate huge volumes of relevant but often underutilized data. This study explores activities undertaken by researchers from the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b), an international research institution that promotes the utilization of their findings in the policymaking processes in Bangladesh. Methods: The study used an exploratory case study design and employed qualitative methods to explore activities implemented to promote research utilization and the extent to which researchers felt that their findings contributed to the policymaking process. Data were collected between September and December 2011 through key informant interviews, focus group discussions with study investigators, and database and document reviews. We reviewed findings from 19 reproductive health studies conducted and completed by icddr,b researchers between 2001 and 2011. We interviewed 21 key informants, including 13 researchers, two policy makers, and six programme implementers. Data were entered into Microsoft Word and analyzed manually following a thematic framework approach. Following the World Health Organization/Turning Research into Practice (WHO/TRIP) framework, three case studies of how research findings were utilized in the policymaking processes in Bangladesh were documented. Results: Activities implemented to promote research utilization included conducting dissemination workshops, publishing scientific papers, developing policy briefs, providing technical assistance to policymakers and programme implementers, holding one-on-one meetings, and joining advocacy networks. The majority of the researchers (12 of 13) reported that their study findings were utilized to influence policymaking processes at different levels. However, some researchers reported being unaware of whether and how their findings were utilized. As regards actual utilization of research findings, the evidence from the three case studies indicate that research findings can be utilized instrumentally, conceptually and symbolically, and at different stages within the policymaking process, including agenda setting and policy formulation and implementation. Conclusions: The results show that research findings from icddr,b were promoted and utilized in health policymaking processes in Bangladesh using a variety of utilization approaches. These results suggest a need for using multiple approaches to promote utilization of research findings in health policymaking processes.
Keywords: Evidence; Health; Policymaking; Research uptake; Research utilization